KARAKTERISTIK PEDAGANG INFORMAL SEBAGAI â€œACTIVITY SUPPORTâ€ KORIDOR JALAN KINTAMANI - BATAM - Cia, Helen; Sarjono, Agung Budi (Jurnal Arsitektur ARCADE, 2019)
Abstract: The Maitreya school and tourists who came to Maha Vihara Duta Maitreya made the Kintamani corridor increasingly active, can be seen by the existence of shops as a formal activity which was followed by the proliferation of informal activities.Informal activities using road shoulder that should be provided as an emergency route are used as a place of activity where this activity also moves the economy and social activities for the road user community, this activity helps especially students, students and the surrounding community to fulfill their needs because of their superior location and more affordable prices, especially when compared to goods and services provided by formal traders.The phenomenon of Informal Activity as the Kintamani corridor support activity is the purpose of the research so that the structuring of the area of informal activities is better and safer for the perpetrators of the activity. The technique of survey primary data collection is through visual observations in the form of observations of "time budget method" and photo media, secondary data collection techniques by searching for the needs of informal activities and the behavior of the perpetrators of these informal activities..Keyword: activity support , informal traders , setting area Abstrak: Sekolah Maitreya dan wisatawan yang datang ke Maha Vihara Duta Maitreya membuat koridor Kintamani semakin meningkat aktivitasnya, bisa dilihat dengan adanya pertokoan sebagai aktivitas formal yang diikuti semakin menjamurnya aktivitas informalnya.Â Â  Aktivitas informal menggunakan bahu jalan yang seharusnya disediakan sebagai jalur darurat digunakan sebagai tempat beraktivitas dimana aktivitas ini juga menggerakkan perekonomian dan aktivitas sosial bagi masyarakat pengguna jalan, aktivitas ini membantu khususnya para siswa, mahasiswa dan masyarakat sekitar dalam memenuhi kebutuhannya karena keunggulannya lokasi yang lebih dekat dan harga yang lebih terjangkau, terutama ketika dibandingkan dengan barang dan jasa yang disediakan oleh pedagang formal.Fenomena Aktivitas Informal sebagai activity support koridor Kintamani inilah yang menjadi tujuan dari penelitian sehingga penataan area aktivitas informal yang menjadi lebih baik dan aman bagi pelaku aktivitas. Tehnik pengumpulan data primer survei dengan observasi visual berupa pengamatan â€œtime budget methodâ€ dan media foto, teknik pengumpulan data sekunder dengan cara mencari kebutuhan dari aktivitas informal dan perilaku pelaku aktivitas informal tersebut. Kata Kunci: Activity Support , Pedagang Informal , Setting Area